The Association between Oxygen Consumption of the Liver Graft and Post-transplant Outcome. - Shiba, Hiroaki; Kelly, Dympna M; Kelly, Dympna M (Medical Research Archives, 2017)
The association between oxygen consumption of the liver graft after reperfusion and post-transplant outcome has been studied from 1950s. The lack of significant progress is because oxygen consumption of the liver graft is determined by various factors, including the donor condition, status of the graft preservation, cold ischemia time, and hepatic blood flow after reperfusion. However, metabolic alterations, such as oxygen consumption and glucose metabolism in the liver grafts are reliable predictors of subsequent the liver graft function, and may help the decision of re-transplantation for the patients with failed liver graft. Appropriate organ preservation reduces oxygen consumption of the liver grafts, and low oxygen consumption might reflect less histological damage after preservation and reperfusion. In contrast, systemic oxygen consumption after reperfusion in patients with successful liver transplantation was higher than systemic oxygen consumption in those with primary non-function and graft dysfunction. This review summarizes association between oxygen consumption of the liver graft and post-transplant outcome.
Keywords: Liver transplantation; Oxygen consumption